2020
DOI: 10.1186/s12909-020-1962-7
|View full text |Cite
|
Sign up to set email alerts
|

Does group cohesion foster self-directed learning for medical students? A longitudinal study

Abstract: Background:The importance of self-directed learning (SDL) and collaborative learning has been emphasized in medical education. This study examined if there were changes in the pattern of SDL and group cohesion from the time of admission to medical school under the criterion-referenced grading system, increased group activities, and interaction of medical education curriculum. Second, it was examined whether group cohesion influences selfdirected learning. Methods: The participants were 106 medical students (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…In the tool, a higher total sum score indicates a higher degree of self-directed learning readiness. The reliability of this tool has been previously demonstrated by a Cronbach's alpha coefficient ranging from 0.84 to 0.94, and this study showed a Cronbach's alpha of 0.91 (Cho & Kim, 2021;Kim & Yang, 2020).…”
Section: Self-directed Learning Readinesssupporting
confidence: 54%
“…In the tool, a higher total sum score indicates a higher degree of self-directed learning readiness. The reliability of this tool has been previously demonstrated by a Cronbach's alpha coefficient ranging from 0.84 to 0.94, and this study showed a Cronbach's alpha of 0.91 (Cho & Kim, 2021;Kim & Yang, 2020).…”
Section: Self-directed Learning Readinesssupporting
confidence: 54%
“…In their study, the medical students’ self-directed learning readiness decreased as students progressed through the medical school. However, the studies of Kim and Yang [ 11 ] and Kidane et al [ 9 ] showed that the self-directed learning readiness scores increased following the introduction of the criterion-referenced grading system with increased group activities [ 11 ] or a hybrid program combining traditional teaching method and PBL [ 12 ]. Although these studies used a different tool to measure self-directed learning in different contexts (face-to-face contexts) from this study, these results seem to indicate the importance of increased learning activities that promote self-directed learning skills.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported significant drops or no differences in the self-directed learning readiness across academic years at medical school [ 12 - 14 ]. Meanwhile, some other studies reported that self-directed learning readiness increased after implementing student-centered learning activities such as problem-based learning (PBL), flipped learning, or additional group activities [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Academic Programs at King Khalid University were applied for academic accreditation that requires a continuous improvement in the academic teaching. This changed the way courses are taught by focusing on the quality of teaching and measuring them using key performance indicators and learning outcomes assessment such as their cognitive competencies, numerical skills and teamwork [22][23][24]. In line with these academic developments, it is worth to address the role of gender in the context of absenteeism and academic achievements in the medical sciences eld.…”
Section: Introductionmentioning
confidence: 99%